CULTISM AND ITS EFFECTS ON THE SOCIETY: IMPLICATIONS ON EDUCATIONAL INSTITUTIONS IN OSUN STATE - Iyanda, D. F. (Sokoto Educational Review, 2020)
One o f the social problems facing Educational institutions today is cultism. The menace of secret cults in educational institutions in general and tertian’ institutions, in particular, has assumed such an alarming proportion in Nigeria that it appears second only to drug trafficking. Therefore, this paper examines secret cults in Nigeria’s higher institutions. It reviews the nature and historical background of cults in Nigeria’s schools. In this paper emphasis is also laid on causes or factors promoting cultism in our institutions of higher learning, the devastating effects involved, the school environment and the innocent law-abiding members of the society and the probable ways of curbing or curtailing secret cults in our society and our institutions of higher learning.